Evaluating medical education in Brazil: analysis of the National Student Performance Exam 2023 - Rufino, Rogerio; Neves, Mario Fritsch Toros; Barbosa, Adauto Dutra Moraes; Povedano, Andrea; Schanaider, Alberto (Frontiers in Medicine, 2025)
BackgroundThe evaluation of medical education in Brazil relies on instruments such as the National Student Performance Exam (ENADE) and the Preliminary Course Concept (PCC), which guide regulation and funding.ObjectivesTo analyze national data from the 2023 ENADE for the medical program, describing variations by administrative category and region, and to discuss implications for building a fairer assessment model aligned with the principles of the Brazilian Unified Health System (SUS).MethodsA descriptive study using consolidated data from 309 Medical Programs participating in ENADE 2023. Mean scores and standard deviations for the continuous PCC (scale 0–5) were calculated by institutional category (federal, state, municipal public institutions, and private with or without profit) and geographic region.ResultsFederal public institutions showed a mean PCC of 2.82 ± 0.38; state, 2.74 ± 0.42; and municipal, 2.65 ± 0.45. Private for-profit institutions had 2.72 ± 0.48, and non-profit institutions 2.85 ± 0.42. The Indicator of Difference Between Observed and Expected Performance (IDOEP) component, which accounts for 35% of the PCC, was higher in for-profit private institutions (3.70 ± 0.68) compared to public ones (2.65 ± 0.50), reflecting limitations in adjusting for socioeconomic intake profiles. Student perception scores were also higher in private institutions (3.85 ± 0.60) than in public ones (3.00 ± 0.55). Regionally, PCC means were higher in the South (3.45 ± 0.40) and Southeast (3.35 ± 0.45) than in the Northeast (2.85 ± 0.55) and North (2.70 ± 0.60).ConclusionResults suggest that the current ENADE/PCC model may mask structural and regional inequalities, favoring institutional strategies focused on large-scale enrollment with lower admission requirements.